2015
DOI: 10.1038/srep12776
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll catalyse the photo-transformation of carcinogenic benzo[a]pyrene in water

Abstract: Algal blooms cause great damage to water quality and aquaculture. However, this study showed that dead algal cells and chlorophyll could accelerate the photo-transformation of benzo[a]pyrene (BaP), a ubiquitous and persistent pollutant with potently mutagenic and carcinogenic toxicities, under visible light irradiation. Chlorophyll was found to be the major active substance in dead algal cells, and generated a high level of singlet oxygen to catalyse the photo-transformation of BaP. According to various BaP me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 55 publications
3
45
0
Order By: Relevance
“…Catalysts 2018, 8, 628 8 of 13 number of the functional groups to sequester additional metal ions. They are also able to significantly accelerate the photodegradation of pollutants, because algae intracellular substances (such as chlorophylls) can absorb light energy and generate reactive species (OH, 1 O2, HOO, O2 − ) [30,31]. This work demonstrates that pure M. aeruginosa can induce the simultaneous photodegradation of TC and Cr(VI) (Figure 4), which is consistent with the previous theory that algae photolysis is a possible strategy for pollutant degradation [32].…”
Section: Analysis Of the Active Species And Discussion Of The Mechanismsupporting
confidence: 90%
See 2 more Smart Citations
“…Catalysts 2018, 8, 628 8 of 13 number of the functional groups to sequester additional metal ions. They are also able to significantly accelerate the photodegradation of pollutants, because algae intracellular substances (such as chlorophylls) can absorb light energy and generate reactive species (OH, 1 O2, HOO, O2 − ) [30,31]. This work demonstrates that pure M. aeruginosa can induce the simultaneous photodegradation of TC and Cr(VI) (Figure 4), which is consistent with the previous theory that algae photolysis is a possible strategy for pollutant degradation [32].…”
Section: Analysis Of the Active Species And Discussion Of The Mechanismsupporting
confidence: 90%
“…Although both slight decrements were observed in each cycle, the M. aeruginosa-PAN/TiO 2 /Ag NF sustained high activity even after three consecutive cycles and 12 h of continuous irradiation. This result is consistent with the previous results showing that the damaged algae was efficient in the photolysis of pollutants [30,32]. These results demonstrate that bionano hybrid nanofibers have relatively high photocatalytic activity and may be recovered and reused in the combined pollutant treatment.…”
Section: Repeated Testsupporting
confidence: 93%
See 1 more Smart Citation
“…Although slight decrements in photocatalytic activity were observed, the algae-TiO2/Ag NF still maintained a high level of activity in successive cycles. A similar phenomenon was found in photo-transformation of aniline and benzo[a]pyrene by algae cells, and the photolysis of pollutants were still efficient in the presence of dead algae cells [26,40]. This finding confirmed that algae-TiO2/Ag NF was stable and effective for the reduction of Cr(VI) and could be easily recovered based on its good settling properties.…”
Section: Repeated Testssupporting
confidence: 72%
“…The photodegradation of Norfloxacin was enhanced with algae concentration and was influenced by temperature and pH of the solution (Zhang et al 2012a). Chlorophyll from dead algal cells has been found to be able to catalyze the photodegradation of benzo[a]pyrene by acting as a photosensitizer (Luo et al 2015). Extracellular secretions from M. aeruginosa have also been found to be able to accelerate the photodegradation of triclosan (Huang et al 2016).…”
Section: Photodegradationmentioning
confidence: 86%